Local Autonomy and Federalism: How Indonesia Deal with Democracy in the Global Governance? - Rodiyah Rodiyah; Ridwan Arifin; Steven Steven (Pandecta Research Law Journal, 2020)
Most countries in the world choose the form of Federal state or Unity within organizing a government. The selection of this form of state based on political, sÃ‚Âocial will include the culture and history of a country. Each form of this country has advantages and disadvantages. The Unitary State emphasizes the administration of government in the government centers and regions in the province do not have extensive autonomy in managing their regions. Unlike the Federal State, where the position of the Federal State and the State are equal. The concept of federalism has been applied in many countries. The state is given the widest possible autonomy to take care of their area. Regional autonomy aims to improve community service, develop democratic life, and encourage the community empowerment to foster creativity. Regional autonomy also has a positive impact and a negative impact on the region. This paper intends to analyze the concept of federalism and regional autonomy with practical analysis in Indonesia.